Implementasi Hak-Hak Anak Tentang Pengakuan Dan Perlindungannya Dalam Perspektif Fiqih Syafi’iyah (Studi Kasus Pengadilan Agama Binjai) - Muammar Hafiz Tanjung; Ahmad Akbar (Journal Smart Law, 2025)
This study discusses the implementation of children's rights concerning their recognition and protection from the perspective of Shafi'i Fiqh (Fiqih Syafi’iyah), with a case study at the Binjai Religious Court (Pengadilan Agama Binjai). The research is motivated by legal issues regarding the status of children, particularly children born out of wedlock, which creates a dilemma in applyingclassical Islamic law and positive law in Indonesia.The objective of this research is to determine th concept of a child in Shafi'i Fiqh, the corresponding children's rights, and their relevance and implementation in the practice of the Binjai Religious Court. The research method uses a qualitative approach with juridical-normative and juridical-empirical methods. Data was obtained throughliterature review, documentation, and interviews with judges at the Binjai Religious Court. The analysis was conducted by correlating Shafi'i Fiqh norms with legal practice in the court.The results show that the concept of a child in Shafi'i Fiqh emphasizes the importance of lineage (nasab), the right to maintenance (nafkah), custody (hadhanah), and child protection from birth. The implementation at the Binjai Religious Court is essentially aligned with Shafi'i Fiqh principles, especially regarding theright to maintenance, care, and education. However, challenges persist in cases of children born out of wedlock, as Shafi'i Fiqh limits lineage only to the mother, while Indonesian positive law grants broader protection. This indicates both relevance and difference, which can be understood through the objectives of Sharia (maqasid al-syari’ah), namely hifz al-nasl (protection of progeny) and hifz al-nafs (protection of life).